Economic Benefits of Renewable Energy Adoption in Developing Countries: A Case Study of Central Asia (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
Renewable energy adoption offers substantial economic advantages for developing countries, including cost savings, job creation, enhanced energy security, and GDP growth, while mitigating fossil fuel dependency and environmental degradation. This article examines these benefits through a general framework for developing economies and a focused case study on Central Asia, a region rich in solar, wind, and hydropower potential yet heavily reliant on hydrocarbons. Drawing on data from the International Renewable Energy Agency (IRENA, 2025) and the International Energy Agency (IEA, 2025), the analysis highlights how renewables can drive sustainable development amid geopolitical and climatic challenges. In Central Asia, adoption has accelerated, with installed capacity reaching 17.3 GW by 2023—a 26.6% increase over five years—yielding benefits like reduced import costs and regional power trade savings estimated at USD 1.5 billion annually (World Bank, 2023; updated projections for 2025). However, barriers such as infrastructure deficits and policy gaps persist. The study employs a qualitative synthesis of economic models and empirical data, advocating for targeted investments to maximize returns. Findings underscore renewables' role in fostering inclusive growth, with implications for policy in resource-constrained regions.